Drought reconstruction based on tree-ring earlywood of Picea obovata Ledeb. for the southern Altay Mountains. Issue 3 (2nd July 2020) - Jiang, Shengxia; Zhang, Tongwen; Yuan, Yujiang; Yu, Shulong; Shang, Huaming; Zhang, Ruibo
ABSTRACT: In this study, a 177-year April–June Palmer Drought Severity Index (PDSI) for the southern slopes of the Altay Mountains (China) was reconstructed based on the earlywood width of 96 Siberian spruce ( Picea obovata Ledeb.) samples located at eight different sites. The reconstructed PDSI tracked the observed data well ( r = 0.723, p < .0001, n = 52). This PDSI reconstruction captures some drought years and periods noted in historical documents, and it agrees well with other hydroclimatic reconstructions for the surrounding area. The 22-, 11-, 2.3-, and 2.1-year cycles of the reconstruction and the spatial correlation with sea surface temperature revealed that the variability of the PDSI for the study area might be influenced by both the Schwabe cycle of solar activity and the interannual oscillation of land–atmosphere–ocean circulation systems. Spatial correlation also showed the reconstruction contained climatic signals, being representative of a larger area extending from northern Xinjiang to northeastern Kazakhstan and a part of southern Russia. Synoptic climatology analysis revealed a relationship between anomalous atmospheric circulation and wet/dry years on the southern slopes of the Altay Mountains in China and its surrounding area.